Cancer cells invade confined microchannels via a self-directed mesenchymal-to-amoeboid transition - Holle, Andrew W.; Spatz, Joachim P. (Nano letters, 2019)
Cancer cell invasion through physical barriers in the extracellular matrix (ECM) requires a complex synergy of traction force against the ECM, mechanosensitive feedback, and subsequent cytoskeletal rearrangement. PDMS microchannels were used to investigate the transition from mesenchymal to amoeboid invasion in cancer cells. Migration was faster in narrow 3 μm-wide channels than in wider 10 μm channels, even in the absence of cell-binding ECM proteins. Cells permeating narrow channels exhibited blebbing and had smooth leading edge profiles, suggesting an ECM-induced transition from mesenchymal invasion to amoeboid invasion. Live cell labeling revealed a mechanosensing period in which the cell attempts mesenchymal-based migration, reorganizes its cytoskeleton, and proceeds using an amoeboid phenotype. Rho/ROCK (amoeboid) and Rac (mesenchymal) pathway inhibition revealed that amoeboid invasion through confined environments relies on both pathways in a time- and ECM-dependent manner. This demonstrates that cancer cells can dynamically modify their invasion programming to navigate physically confining matrix conditions.
Gesehen am 22.05.2019